2023
DOI: 10.55446/ije.2023.700
|View full text |Cite
|
Sign up to set email alerts
|

T-Perches Determining Avian Feeding Guilds in Maize

Abstract: Avian diversity is considered an environmental indicator for measuring ecosystem quality. The availability of food and its diverse types influence bird distribution and their community structure in agricultural landscapes. The current study investigated the role of T-perches as bird attractants in maize at the Punjab Agricultural University, Ludhiana. A total of 39 species were observed belonging to 12 orders and 24 families. Insectivorous birds were observed as the most dominant feeding guild constituting 47.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In the present study, the COD values for surface water and groundwater were similar to those found in Chandigarh city, which indicates that the COD values originated from anthropogenic activities (Kaur and Malik, 2012). A recent research showed that many species of birds also live in and around the surface water (water ponds) in Barnala District of Punjab State (Kaur et al, 2018).During the period in which this study was conducted, ducks were seen in the ponds visited,whichis a sign of microbiological activity and poor water quality. The disposal of various types of domestic and commercial waste in the ponds may lead to the entering and biomagnifications of contaminants in theaquatic food chain by affecting the COD levels in surface water.…”
Section: Wqisupporting
confidence: 84%
See 3 more Smart Citations
“…In the present study, the COD values for surface water and groundwater were similar to those found in Chandigarh city, which indicates that the COD values originated from anthropogenic activities (Kaur and Malik, 2012). A recent research showed that many species of birds also live in and around the surface water (water ponds) in Barnala District of Punjab State (Kaur et al, 2018).During the period in which this study was conducted, ducks were seen in the ponds visited,whichis a sign of microbiological activity and poor water quality. The disposal of various types of domestic and commercial waste in the ponds may lead to the entering and biomagnifications of contaminants in theaquatic food chain by affecting the COD levels in surface water.…”
Section: Wqisupporting
confidence: 84%
“…In rural areas of the state, many village ponds serve for rainwater harvesting, livestock bathing and irrigation (Ansal et al, 2010). Due to the household wastewater discharges in the statevillage ponds, the later are rich in nutrients, which attract many species of migratory and local birds (Kaur et al, 2018).The state of Punjab is characterized by significant production of Bharat bricks (fired bricks), as about 2500 brick production units withmore than 2 lakh workersis a prominent non-agro-based industry in the state (Kainth, 2009). To draft the study plan, a pilot survey was first conducted to locate the brick kilns on Google Earth.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations